Implementasi Kebijakan Layanan Peminjaman Terbatas Pada Koleksi Cadangan di UPT Perpustakaan Universitas Andalas - Yn, Afriani Indah Rupika; Nabila, Jeihan (Departemen Informasi Perpustakaan dan Kearasipan, 2023)
This research is motivated by the implementation of a lending service policy limited to reserve collections. This research aims to describe the implementation of the limited loan service policy for reserve collections at the Andalas University Library. The method used in this research is a qualitative descriptive method. Data collection was carried out by means of interviews and documentation. This data analysis technique is carried out in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that: (1) Standards and objectives have not been implemented properly. (2) Resources have not been implemented, where the resources for facilities and infrastructure have not been met. Therefore, to achieve success, the policy of facilities and infrastructure must be met. (3) The characteristics of the organization or implementing agency that have been implemented in lending services are limited to reserve collections. (4) The attitude of implementing the service policy has been implemented, because the implementers in realizing limited lending services for reserve collections are also enthusiastic in implementing limited lending services for reserve collections. (5) Inter-organizational communication in implementing limited loan services for reserve collections has been implemented in a harmonious manner, the results provided from this impact have also become part of the form of inter-organizational communication implemented in the limited loan service policy for reserve collections at the Andalas University Library.